Prescribing for moderate or severe unipolar depression in patients under the long-term care of UK adult mental health services - Carol Paton; Ian M. Anderson; Philip J. Cowen; Oriana Delgado; Thomas R. E. Barnes (SAGE Publishing, 2020)
Background: A quality improvement programme addressing prescribing practice for depression was initiated by the Prescribing Observatory for Mental Health. Methods: A baseline clinical audit against evidence-based practice standards was conducted in UK adult mental health services. Results: A total of 55 mental health services submitted data for 2082 patients, under the care of a community psychiatric team (CMHT) for at least a year, with a diagnosis of moderate or severe unipolar depression, 54% of whom had a comorbid psychiatric diagnosis. Selective serotonin reuptake inhibitors were prescribed for 35% of the patients, other newer generation antidepressants for 60%, tricyclic antidepressants for 6% and monoamine oxidase inhibitors for <1%. The most commonly prescribed individual antidepressants were mirtazapine (33%, usually in combination with another antidepressant), venlafaxine (25%) and sertraline (21%). Patients with severe depression were more likely ( p  < 0.001) to be co-prescribed an antipsychotic medication, lithium, or to have received electroconvulsive therapy. There was a documented clinical review in the last year in 85%, with a symptom rating scale used in 11%. A documented comprehensive treatment history was accessible for 50% of those prescribed antidepressant medication. Conclusion: Patients with moderate or severe depression remaining under the care of a CMHT for longer than a year are clinically complex. The failure to achieve a level of wellness allowing discharge from mental health services may be partly related to the finding that not all patients had the benefit of a systematic approach to clinical assessment and sequential testing of available evidence-based pharmacological interventions.